Analisis Pemanfaatan Kecerdasan Buatan (AI) Terhadap Berpikir Kritis Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi UIN Syarif Hidayatullah Jakarta - Nida Nadia Najla Mawaddah; Dina Rustiani Agustina; Nur Syarifa Amalia; Iqbal Teguh Raharjo; Firdaus Choirul Amin (CV. ITTC INDONESIA, 2025)
In recent years, artificial intelligence (AI) technology has been increasingly used in education, including by students at the Faculty of Da'wah and Communication Sciences, UIN Syarif Hidayatullah Jakarta. This study aims to determine the pattern of AI utilization in students' academic activities and the extent to which its use affects critical thinking skills. This study uses a quantitative approach with a survey method distributed to active students who have used AI technology such as ChatGPT, Grammarly, and similar tools in their learning process. The results of the analysis show that there is a significant influence between the use of AI and students' critical thinking skills, with an R Square value of 0.488. This means that almost half of the variation in students' critical thinking skills can be explained by the intensity and how they use AI. These findings show that AI not only functions as a technical tool, but is also able to support students' analytical, reflective, and evaluative processes if used strategically. However, the results also show that there are still 51.2% other factors that play a role, so the use of AI needs to be balanced with an awareness of the importance of independent thinking. This research is expected to be a consideration for students in using AI wisely and become a reference for educational institutions in designing technology utilization policies that support the development of students' reasoning abilities.